2017
DOI: 10.1111/imcb.1032
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DR+ NK cells are mostly characterized by less mature phenotype and high functional activity

Abstract: NK cells change their phenotype and functional characteristics during activation. In this work, we searched for a relationship of HLA-DR expression with differentiation stages and functional activity of NK cells ex vivo and stimulated in vitro with IL-2 challenged with gene modified feeder K562 cells expressing membrane-bound IL-21 (K562-mbIL21). This stimulation technique has been described for NK cell expansion in clinical use. We have observed that HLA-DR expression in freshly isolated circulating NK cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
89
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 46 publications
15
89
2
Order By: Relevance
“…This is an interesting finding, as it has been described that CD56 hi NK cells normally express HLA-DR to a higher degree than CD56 dim NK subsets (43,44). Intriguingly, it has been shown that CD56 dim HLA-DR + NK cells develop during pro-inflammatory conditions (45) and have better stimuli-induced secretion of IFN-γ than their HLA-DR − counterparts (44,45). Another function attributed to CD56 dim HLA-DR + NK cells is their capacity to induce differentiation of naïve CD4 + T cells into pre-central memory T cells (45).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This is an interesting finding, as it has been described that CD56 hi NK cells normally express HLA-DR to a higher degree than CD56 dim NK subsets (43,44). Intriguingly, it has been shown that CD56 dim HLA-DR + NK cells develop during pro-inflammatory conditions (45) and have better stimuli-induced secretion of IFN-γ than their HLA-DR − counterparts (44,45). Another function attributed to CD56 dim HLA-DR + NK cells is their capacity to induce differentiation of naïve CD4 + T cells into pre-central memory T cells (45).…”
Section: Discussionsupporting
confidence: 52%
“…An expansion of two CD56 dim NK subsets, expressing HLA-DR at a higher intensity than CD56 hi NK cells, was also detected in samples from patients with HT. This is an interesting finding, as it has been described that CD56 hi NK cells normally express HLA-DR to a higher degree than CD56 dim NK subsets (43,44). Intriguingly, it has been shown that CD56 dim HLA-DR + NK cells develop during pro-inflammatory conditions (45) and have better stimuli-induced secretion of IFN-γ than their HLA-DR − counterparts (44,45).…”
Section: Discussionmentioning
confidence: 53%
“…Examining a broader range of NK phenotypic markers ( Figure 4A) confirmed these differences in maturity. Patients had a significantly higher proportion of NK cells bearing markers associated with NK immaturity (CD25, CD27, CD127 and HLA-DR) 34,35,36,37 and a significantly lower proportion of NK cells bearing markers associated with NK maturity (CD45RA and CD57) 38,39 . No difference was observed in the proportion of NK cells expressing the adhesion molecule CD11b 40 , the adhesion molecule and ectoenzyme CD38 41 nor CD161, expressed by a distinct subtype of pro-inflammatory NK cells 42 .…”
Section: Nk Cells In Patients Are Shifted To An Immature Phenotypementioning
confidence: 99%
“…NK cells have been shown to regulate immune cell responses of T cells (Waggoner et al, 2011;Cook et al, 2014;Crouse et al, 2015), antigen-presenting cells (Andrews et al, 2005;Moretta et al, 2005;Alter et al, 2010;Altfeld et al, 2011;Michel et al, 2012), and indirectly B cells (Rydyznski et al, 2015(Rydyznski et al, , 2018, all of which express HLA-II molecules. In addition, NK cells themselves are able to express HLA-II molecules (Sedlmayr et al, 1996;Erokhina et al, 2018;Costa-Garcia et al, 2019), implicating that a potential interaction between HLA-II and NK cell receptors can not only occur in trans but also in cis. The identification of HLA-II molecules as ligands for NK cell receptors now provides a possible molecular mechanism to investigate the immune cross-talk between NK cells and HLA-II-expressing immune cells, and the implications for immune responses against malignant cells and pathogens.…”
Section: Hla Class II Molecules Can Serve As Ligands For Nk Cell Recementioning
confidence: 99%